Adenylation and exosome-mediated degradation of cotranscriptionally cleaved pre-messenger RNA in human cells. - West, S; Gromak, N; Norbury, C; Proudfoot, N (2006)
In humans, polyadenylation of messenger RNA (mRNA) protects transcripts from degradation and enhances translation efficiency. Conversely, in bacteria, polyadenylation destabilizes mRNA. RNA adenylation was recently implicated in promoting degradation of some yeast RNAs by the exosome. The exosome complex of exoribonucleases is a major degradation machine in eukaryotes, and many of its components share significant homology with bacterial exonucleases. The human beta-globin pre-mRNA is cotranscriptionally cleaved within its 3' flank. Here, we show that some RNA ends, coinciding with these cotranscriptionally cleaved regions, contain short A tails on their 3' ends. Moreover, all of the pre-mRNA species detected accumulate in the absence of the exosome. We have also detected adenylation on RNA 3' ends originating within the mouse serum albumin (MSA) 3' flanking region RNA. This step in pre-mRNA degradation may represent an additional role for adenylation in mammals.